Effects of Nitric Oxide Synthase Inhibition on Cutaneous Vasodilation in Response to Acupuncture Stimulation in Humans. Issue 1 (March 2013) - Kimura, Kenichi; Takeuchi, Hayato; Yuri, Kuniko; Wakayama, Ikuro
Objectives: The aim of the present study was to elucidate the mechanism of cutaneous vasodilation following acupuncture stimulation by investigating the roles of nitric oxide (NO) and axon reflex vasodilation. Methods: The subjects were 17 healthy male volunteers. The role of NO was investigated by administering N G -nitro-L-arginine methyl ester hydrochloride (L-NAME, 20 mM), an NO synthase inhibitor or Ringer's solution (control site), via intradermal microdialysis (protocol 1; n=7). The role of axon reflex vasodilation by local sensory neurones was investigated by comparing vasodilation at sites treated with 'eutectic mixture of local anaesthetics' (EMLA) cream (2.5% lidocaine and 2.5% prilocaine) with untreated sites (control site) (protocol 2; n=10). After 5 min of baseline recording, acupuncture was applied to PC4 and a control site in proximity to PC4 for 10 min and scanning was performed for 60 min after acupuncture stimulation. Skin blood flow (SkBF) was evaluated by laser Doppler perfusion imaging. Cutaneous vascular conductance (CVC) was calculated from the ratio of SkBF to mean arterial blood pressure. Results: In the first protocol, sites administered L-NAME showed significant reductions in CVC responses following acupuncture stimulation compared to control sites (administered Ringer's solution) (p<0.05). In the second protocol, changes in CVC responses after acupuncture stimulation did not differ significantly between treated sites with EMLA cream and untreated sites (p>0.05). Conclusions: These data suggest that cutaneous vasodilation in response to acupuncture stimulation may not occur through an axon reflex as previously reported. Rather, NO mechanisms appear to contribute to the vasodilator response.